Antisolvent Crystallization of Erythromycin Ethylsuccinate in the Presence of Liquid–Liquid Phase Separation - Li, Xiang; Yin, Qiuxiang; Zhang, Meijin; Hou, Baohong; Bao, Ying; Gong, Junbo; Hao, Hongxun; Wang, Yongli; Wang, Jingkang; Wang, Zhao (Industrial & engineering chemistry research, 2016)
The nucleation point of erythromycin ethylsuccinate crystallization with liquid–liquid phase separation, also called oiling-out, was determined through nucleation analysis. To achieve successful monitoring of nucleation events, focused beam reflectance measurements were performed during antisolvent crystallization. The induction time of the oiling-out system was determined and correlated with classical nucleation theory. The induction time increases with decreasing solubility under a constant thermodynamic driving force. The position of a nucleation point may be determined by comparing the nucleation energy barrier and supersaturation generated in solute-rich and solute-lean phases. The estimated interfacial energy is in the range of 0.422–1.315 m·J/m2, which is in agreement with nucleation theory. A homogeneous nucleation process was observed under high supersaturation, and heterogeneous nucleation took place at low supersaturation. The growth mechanism was identified with the interfacial tension. The continuous growth dominates the whole growth process.